IMPLEMENTASI PENGENDALIAN SEDIAAN OBAT DENGAN METODE ECONOMIC ORDER QUANTITY PADA RS.X DI MARTAPURA, KALIMANTAN SELATAN - Yunike Senopadang; Stefanus Budy Widjaja S.; Fitri Novika Widjaja (Perpustakaan Universitas Surabaya, 2020)
This study aims to implement the method of controlling the supply ofmedicines at the RS.X Pgarmacy Installation in Martapura, because it is less precise inestimating the demand resulting in the purchase of excess stock. Therefore, this studyaims to know and analyze the control of drug preparations on RS.X Pharmacy Installation by applying the Economic Order Quantity method and determining thecorrect forecasting.Implementation of this inventory control using EOQ method, calculation ofOrder Frequency, Booking Interval, Safety Stock, Reorder Point, and MaximumInventory. Service Stock used is 99%. Inventory costs can be determined by calculatingthe relevant costs, such as: purchase costs, ordering costs, and storage costs.After processed and then analyzed the comparison of inventory cost calculationresults between using EOQ methodwith business entity policy. The result 8% savingsusing EOQ method.